2013
DOI: 10.1186/1746-6148-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with an attenuated Salmonella Gallinarum mutant as a fowl typhoid vaccine with a live adjuvant strain secreting the B subunit of Escherichia coliheat-labile enterotoxin

Abstract: BackgroundThe Salmonella Gallinarum (SG) lon/cpxR deletion mutant JOL916 was developed as a live vaccine candidate for fowl typhoid (FT), and a SG mutant secreting an Escherichia coli heat-labile enterotoxin B subunit (LTB), designated JOL1229, was recently constructed as an adjuvant strain for oral vaccination against FT. In this study, we evaluated the immunogenicity and protective properties of the SG mutant JOL916 and the LTB adjuvant strain JOL1229 in order to establish a prime and boost immunization stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Cell-mediated immune responses can be represented by the SI of lymphocytes by using a specific antigen [ 2 19 ]. Significant cell-mediated immune responses were shown by the peripheral blood lymphocyte proliferation assay in both the C79-13Δ crp Δ asd (pYA-HN) and NDV live vaccine groups to be greater than that of the control group at 21 days after immunization ( p < 0.05) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-mediated immune responses can be represented by the SI of lymphocytes by using a specific antigen [ 2 19 ]. Significant cell-mediated immune responses were shown by the peripheral blood lymphocyte proliferation assay in both the C79-13Δ crp Δ asd (pYA-HN) and NDV live vaccine groups to be greater than that of the control group at 21 days after immunization ( p < 0.05) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, research into attenuated Salmonella as an oral live vaccine vector to carry and express exogenous protective antigen genes of pathogens has become popular. It has been reported that using attenuated Salmonella to construct recombinant live vaccines not only has the ability to activate the body's immune system to resist Salmonella infection, but it also can significantly enhance the immune effect of the exogenous gene being carried [ 18 19 27 30 35 ]. In this study, the survival rates of the chicken challenged chicken with the C79-13 strain after immunization with C79-13Δ crp Δ asd (pYA-HN) or C79-13Δ crp Δ asd (pYA) were 100% ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we used live attenuated SG secreting LTB (JOL1229) as an adjuvant for JOL916 (Jeon et al, 2012(Jeon et al, , 2013. However, such adjuvant-vaccine compositions may be inconvenient to implement in the poultry industry due to uneconomical formulations.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, an oral vaccination with S. Gallinarum increases plasma IgG, intestinal secretory IgA and cell-mediated responses (Jeon et al, 2013). In study of immune responses, S. Enteritidis, S. Gallinarum and S. Pullorum stimulated expressions differently of cytokine and chemokine gene of cecal tonsil in newly hatched chicks and older chickens (Setta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%